2011
DOI: 10.1088/0004-6256/143/1/16
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Wavelength Goals Observations of Star Formation and Active Galactic Nucleus Activity in the Luminous Infrared Galaxy Ic 883

Abstract: New optical Hubble Space Telescope (HST), Spitzer Space Telescope, Galaxy Evolution Explorer, and Chandra observations of the single-nucleus, luminous infrared galaxy (LIRG) merger IC 883 are presented. The galaxy is a member of the Great Observatories All-sky LIRG Survey and is of particular interest for a detailed examination of a luminous late-stage merger due to the richness of the optically visible star clusters and the extended nature of the nuclear X-ray, mid-IR, CO, and radio emission. In the HST Advan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Their overall properties indicate they are SCs and associations similar to those observed in other galaxies undergoing extensive bursts of star formation. The detection method followed the procedure described in detail by Modica et al (2012) for SCs in the late stage LIRG merger IC 883. First, masks outlining the galaxy were applied to the images.…”
Section: Cluster Detection and (B − I) Color Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Their overall properties indicate they are SCs and associations similar to those observed in other galaxies undergoing extensive bursts of star formation. The detection method followed the procedure described in detail by Modica et al (2012) for SCs in the late stage LIRG merger IC 883. First, masks outlining the galaxy were applied to the images.…”
Section: Cluster Detection and (B − I) Color Mapmentioning
confidence: 99%
“…Then Source Extractor (Bertin & Arnouts 1996) was used to fit and subtract the underlying galaxy and perform point-source detection in the B-and I-band images. The extracted objects were processed with IDL routines to perform photometry and apply selection criteria that accepted only reliable sources with an FWHM of 1.7-4 pixels, have S/N > 5, and are detected in both bands; details are given in Modica et al (2012). This procedure resulted in the detection of 120 point sources with 21 mag B 27 mag and 19.5 mag I 25.7 mag (uncorrected for extinction); their coordinates and photometric properties are listed in the Appendix (Table 15).…”
Section: Cluster Detection and (B − I) Color Mapmentioning
confidence: 99%
“…This LIRG is probably the result of the merger of two disc galaxies (Smith et al 1995), as suggested by its associated tidal tails, a diffuse one approximately perpendicular to the region where gas and dust preferentially concentrate (i.e., the disc) as seen in optical and near-IR (NIR) studies (e.g., Smith et al 1995;Scoville et al 2000;Modica et al 2012), and a narrow one along the disc itself (Keel 1985).…”
Section: Introductionmentioning
confidence: 94%
“…However, Yuan et al (2010) reclassified this galaxy as a composite starburst-AGN, based on the revised optical diagnostic diagrams of Kewley et al (2006). The multi-wavelength study of IC 883 by Modica et al (2012) also provides evidence of its composite nature. It is consequently expected that an AGN contributes to A&A 543, A72 (2012) Notes.…”
Section: Introductionmentioning
confidence: 99%
“…A multiwavelength study of the late-stage merger IC 883 (Modica et al 2012) revealed 156 star clusters located primarily in the circumnuclear region (3-7 kpc from the mid-IR core) and throughout the tidal tails. The clusters have a luminosity function similar to clusters in other star-forming galaxies, and the broadband colors are consistent with a starburst population synthesis model with ages of approximately 10 7 − 10 9 yr, or as young as a few Myr considering the (unknown) extinction.…”
Section: Detailed Multiwavelength Studies Of Individual Systemsmentioning
confidence: 99%